Produk Kredit Pemilikan Rumah Bank Syariah Indonesia Parepare (Antara Peran Dan Risiko) - Arifin, Asriadi (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2024)
The purpose of this research is to examine the mortgage financing products (KPR) at BSI with a review of the contestation between roles and risks. The research results are expected to contribute well to the development of further research. This type of research is descriptive qualitative by explaining in a narrative manner the results of more concrete and in-depth research relating to the technical aspects of Indonesian Islamic Bank (BSI) in channeling sharia-based KPR housing finance. The research subject is the Indonesian Islamic Bank (BSI) Parepare Branch. The research results were obtained by observing and using participatory interview instruments with the Consumer Processing Head. The results of the study show that Islamic banking is faced with a dilemma between carrying out its role in creating a conducive economy nationally and at the same time responding to the needs of society collectively. Through this role, banks obtain returns in the form of profits (profitability). However, in addition to obtaining profits, banks are also faced with a higher level of risk. With it, to maintain the existence of Islamic banking, it must receive collective support from all existing stakeholders. Consideration of risk in Islamic banking must also necessitate the management of financing in banks which pays more attention to the principle of prudence with good risk management and analysis, because between profit and risk, the two have an inherent (inherent) relationship that cannot be avoided.